Debye Representation of Frequency Dependent Ground for LEMP Analysis With RC-FDTD - Kurnaz, Osman; Aksoy, Serkan (IEEE-Inst Electrical Electronics Engineers Inc, 2022)
Finite-difference time-domain (FDTD) method combined with the recursive convolution technique is applied to compute lightning electromagnetic pulses (LEMP) for dispersive ground adopting Longmire and Smith (LS) model in two-dimensional cylindrical coordinates. The novelty of our study is that, to the best of our knowledge, the LEMP simulation has been realized in the time-domain for the first time by directly using the parameters of the LS dispersive soil model by treating the ground as a multipole Debye medium without using approximate techniques such as vector fitting. As a numerical example, the LEMP is simulated above and under the dispersive ground with buried rock formation, which is also modeled as the dispersive Debye medium. The performed simulations are compared at distances of 500 m, 5 km, and 50 km away from the lightning channel for both first stroke and subsequent stroke. The results show that the case of dispersive ground and the rock leads to a difference of up to 61.77% with respect to using constant electrical parameters.
Keywords: Dispersion; Soil; Mathematical models; Time-domain analysis; Finite difference methods; Conductivity; Permittivity; Debye model; dispersive (frequency-dependent) ground; finite-difference time-domain (FDTD); lightning; Longmire and Smith (LS) model; recursive convolution (RC)